2022
DOI: 10.1101/2022.04.20.22274097
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Accuracy of US CDC COVID-19 Forecasting Models

Abstract: Accurate predictive modeling of pandemics is essential for optimally distributing resources and setting policy. Dozens of case predictions models have been proposed but their accuracy over time and by model type remains unclear. In this study, we analyze all US CDC COVID-19 forecasting models, by first categorizing them and then calculating their mean absolute percent error, both wave-wise and on the complete timeline. We compare their estimates to government-reported case numbers, one another, as well as two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Since they rely on the most recent available observational data, model-free recency-type heuristics, such as recency heuristic I and II usually perform well when forecasting over short time horizons. Previous studies have demonstrated that recency heuristic I can provide more accurate forecasts than Google Flu Trends ( 101 ), and that recency heuristic II can compete favorably with CDC and ECDC COVID-19 ensemble forecasting models ( 102 , 104 ). However, simple data-driven heuristics do not typically yield reliable long-term forecasts, as they lack the ability to account for underlying population-level dynamics.…”
Section: Methodsmentioning
confidence: 99%
“…Since they rely on the most recent available observational data, model-free recency-type heuristics, such as recency heuristic I and II usually perform well when forecasting over short time horizons. Previous studies have demonstrated that recency heuristic I can provide more accurate forecasts than Google Flu Trends ( 101 ), and that recency heuristic II can compete favorably with CDC and ECDC COVID-19 ensemble forecasting models ( 102 , 104 ). However, simple data-driven heuristics do not typically yield reliable long-term forecasts, as they lack the ability to account for underlying population-level dynamics.…”
Section: Methodsmentioning
confidence: 99%
“…A number of works demonstrated the effectiveness of neural network models based on Long Short-Term Memory layers (LSTM) [1,6,8]. A recent study [9] showed that the effectiveness of the existing methods applied to the COVID-19 dynamics forecasting is comparable to the estimates based on the "tomorrow as today" method, which indicates the complexity of the task and the need for further improvement of predictive methods. In our previous works [5,7] it was shown that: 1) the accuracy of machine learning models strongly depends on the number of training samples, 2) the usage of the models of this type is inefficient on short prediction horizons (up to 28 days).…”
Section: Pos(dlcp2022)025mentioning
confidence: 99%
“…Some infectious diseases are transmitted through "bites" from insect vectors, while others can be caused by ingesting contaminated food or water (who.int). The WHO, U.S. NIH, U.S. AID, U.S. CDC, and the international scientific community has long recognized the need to develop a comprehensive education, prediction, and prevention system for CDs (13,26,27).…”
Section: Introductionmentioning
confidence: 99%